The effects of cold water immersion on the amount and quality of sleep obtained by elite cyclists during a simulated hill climbing tour - Lastella, M.; Roach, G. D.; Halson, S. L.; Sargent, C. (Sport Sciences for Health, 2019)
Background: The aim of the present study was to examine the effects of cold water immersion on the amount and quality of sleep obtained by elite cyclists during a simulated hill climbing tour. Methods: Ten male professional cyclists (age 21.1±1.7 years) from the Australian Institute of Sport were monitored for eight consecutive nights during a simulated hill climbing tour. The experiment employed a randomised cross over design. Cyclists followed a simulated hill climbing tour consisting of two 3-day sessions (140-190 km per day) separated by 2 days where ~60 km recovery rides were performed. During the first 3 days of simulated competition, five participants underwent a hydrotherapy recovery session (cold water immersion; 11-12 °C for 10 min), while the remaining five participants completed a placebo (ultrasound turned off; 10 min) recovery session. Recovery sessions were completed within 30 min of the conclusion of each competitive session (hh:mm; 13:00-14:00). After 2 days of recovery, participants reversed conditions. Results: Paired samples t tests revealed no differences in the amount and quality of sleep obtained by elite cyclists between conditions. Sleep latency was shorter in the cold water immersion condition compared to the placebo condition (p=0.03). With the exception of sleep latency, sleep/wake behaviours were similar between the cold water immersion and placebo conditions (p>0.05). Conclusion: Cold water immersion did not affect the sleep of elite athletes within this sample. If coaching staff are using cold water immersion as a post-exercise recovery strategy, they may continue to utilise this form of recovery without any impact on their athlete sleep.